2010
DOI: 10.1126/scisignal.2000468
|View full text |Cite
|
Sign up to set email alerts
|

AAA+ Proteins RUVBL1 and RUVBL2 Coordinate PIKK Activity and Function in Nonsense-Mediated mRNA Decay

Abstract: Phosphatidylinositol 3-kinase-related protein kinase (PIKK) family proteins play essential roles in DNA-based and RNA-based processes, such as the response to DNA damage, messenger RNA (mRNA) quality control, transcription, and translation, where they contribute to the maintenance of genome integrity and accurate gene expression. The adenosine triphosphatases associated with diverse cellular activities (AAA+) family proteins RuvB-like 1 (RUVBL1) and RUVBL2 are involved in various cellular processes, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
198
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(219 citation statements)
references
References 63 publications
(106 reference statements)
17
198
1
Order By: Relevance
“…Reptin mutants retained the same subcellular distribution as WT Reptin, and also their ability to partner with Pontin, suggesting that they had no gross defects besides the loss of ATPase activity that could explain their phenotypic effects. We and others have previously shown that Reptin silencing induced the codepletion of Pontin, via a posttranslational mechanism (4,7,20). However, we show here that cells reconstituted with the Reptin Walker B mutants expressed normal levels of Pontin such as those reconstituted with WT siRNA-resistant Reptin (20), thus ruling out that some of the effects seen with the mutants might be due to the loss of Pontin.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Reptin mutants retained the same subcellular distribution as WT Reptin, and also their ability to partner with Pontin, suggesting that they had no gross defects besides the loss of ATPase activity that could explain their phenotypic effects. We and others have previously shown that Reptin silencing induced the codepletion of Pontin, via a posttranslational mechanism (4,7,20). However, we show here that cells reconstituted with the Reptin Walker B mutants expressed normal levels of Pontin such as those reconstituted with WT siRNA-resistant Reptin (20), thus ruling out that some of the effects seen with the mutants might be due to the loss of Pontin.…”
Section: Discussioncontrasting
confidence: 50%
“…Indeed, together with Pontin, Reptin is involved in the assembly of telomerase and their silencing leads to a decreased telomerase activity (4,9). It also controls the levels of all members of the phosphatidylinositol 3-kinase-related protein kinases family, notably mTOR, with Reptin silencing leading to decreased mTOR level and a consequent defect in signaling through S6 kinase (7). Our data also lead us to conclude accordingly that antagonists of Reptin ATPase activity may be of benefit for the therapy of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we showed that Tti1 could interact with all other PIKK family proteins. During revision of this report, Tti1 was also reported as an SMG-1-interacting protein with the name of SMG-10, which further interacts with RUVBL1 and RUVBL2 (37).…”
Section: Discussionmentioning
confidence: 99%